KEMAMPUAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGONTROL PERILAKU SISWA DI MA MIFTAHUL JANNAH KECAMATAN PENINJAUAN - Cahyono, Aris Eko; Alam, Fihris Kholifatul (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This study aims to determine the Ability of Islamic Religious Education Teachers, Controlling student behavior at MA Miftahul Jannah Peninjauan, Efforts of Islamic Religious Education Teachers in controlling student behavior at MA Miftahul Jannah Peninjauan. This study uses a qualitative method. Data collection techniques in this study are observation, interviews and documentation. The data sources used in this study are primary data sources and secondary data sources. while the objects of research are the principal, Islamic Religious Education teachers, homeroom teachers, and students at MA Miftahul Jannah Peninjauan. The results of this qualitative study indicate that the religious behavior of students at MA Miftahul Jannah Peninjauan is in accordance with the religious behavior taught in Islam, such as: saying hello before entering the classroom, being polite to others who pass in front of the teacher without permission, being obedient in worship (not reading prayers before starting lessons and not reading the Qur'an). The efforts of Islamic Religious Education Teachers in forming the religious behavior of students at MA Miftahul Jannah Peninjauan are that teachers use methods to control religious behavior, teachers see and understand the religious behavior of students, control students in maintaining their religious behavior, develop religious behavior through Islamic Religious Education lessons, and provide punishment.